Concomitant Use of NSAIDs or SSRIs with NOACs Requires Monitoring for Bleeding - Lee, Min-Taek; Park, Kwang-Yeol; Kim, Myo-Song; You, Seung-Hun; Kang, Ye-Jin; Jung, Sun-Young (Yonsei medical journal, 2020)
Non-vitamin K antagonist oral anticoagulants (NOACs) are widely used in patients with atrial fibrillation (AF) because of their effectiveness in preventing stroke and their better safety, compared with warfarin. However, there are concerns for an increased risk of bleeding associated with concomitant use of non-steroidal anti-inflammatory drugs (NSAIDs) or selective serotonin reuptake inhibitors (SSRIs) with NOACs. In this study, we aimed to evaluate the risk of bleeding events in individuals taking concomitant NSAIDs or SSRIs with NOACs after being diagnosed with AF.PURPOSENon-vitamin K antagonist oral anticoagulants (NOACs) are widely used in patients with atrial fibrillation (AF) because of their effectiveness in preventing stroke and their better safety, compared with warfarin. However, there are concerns for an increased risk of bleeding associated with concomitant use of non-steroidal anti-inflammatory drugs (NSAIDs) or selective serotonin reuptake inhibitors (SSRIs) with NOACs. In this study, we aimed to evaluate the risk of bleeding events in individuals taking concomitant NSAIDs or SSRIs with NOACs after being diagnosed with AF.A nested case-control analysis to assess the safety of NSAIDs and SSRIs among NOAC users with AF was performed using data from Korean National Health Insurance Service from January 2012 to December 2017. Among patients who were newly prescribed NOACs, 1233 cases hospitalized for bleeding events were selected, and 24660 controls were determined.MATERIALS AND METHODSA nested case-control analysis to assess the safety of NSAIDs and SSRIs among NOAC users with AF was performed using data from Korean National Health Insurance Service from January 2012 to December 2017. Among patients who were newly prescribed NOACs, 1233 cases hospitalized for bleeding events were selected, and 24660 controls were determined.The risk of bleeding events was higher in patients receiving concomitant NSAIDs [adjusted odds ratio (aOR) 1.41; 95% confidence interval (CI) 1.24-1.61] or SSRIs (aOR 1.92; 95% CI 1.52-2.42) with NOACs, compared to no use of either drug, respectively. The risk of upper gastrointestinal bleeding was higher in patients receiving concomitant NSAIDs or SSRIs without proton pump inhibitors (PPIs) (NSAIDs: aOR 2.47; 95% CI 1.26-4.83, SSRI: aOR 10.8; 95% CI 2.41-2.48) compared to no use.RESULTSThe risk of bleeding events was higher in patients receiving concomitant NSAIDs [adjusted odds ratio (aOR) 1.41; 95% confidence interval (CI) 1.24-1.61] or SSRIs (aOR 1.92; 95% CI 1.52-2.42) with NOACs, compared to no use of either drug, respectively. The risk of upper gastrointestinal bleeding was higher in patients receiving concomitant NSAIDs or SSRIs without proton pump inhibitors (PPIs) (NSAIDs: aOR 2.47; 95% CI 1.26-4.83, SSRI: aOR 10.8; 95% CI 2.41-2.48) compared to no use.When NSAIDs or SSRIs are required for NOAC users with AF, physicians need to monitor bleeding events and consider the use of PPIs, especially for combined use of both drugs or when initiating NOACs treatment.CONCLUSIONWhen NSAIDs or SSRIs are required for NOAC users with AF, physicians need to monitor bleeding events and consider the use of PPIs, especially for combined use of both drugs or when initiating NOACs treatment.